Efficacy of VERIGENE® Blood Culture Assays in Accurately and Rapidly Detecting Gram-Negative and Gram-Positive Pathogens - Guevara, Roberto; Davis, Monique G.; Davis, Michelle A.; Ahmed, Sara; Shah, Sidra; Cuaron, Karla; Antony, Suresh J. (Infectious Disorders - Drug Targets, 2022)
Background: Rapid administration of appropriately indicated antibiotics is crucial in septic patients. Sepsis data supports that there is a higher risk of mortality for each hour delay from triage to antibiotic therapy, as well as for inappropriate antibiotic selection. There are a variety of rapid microbial detection systems, such as VERIGENE®, used in acute care facilities to rapidly detect bacteremia and identify resistance markers. Our study investigates the usefulness of VERIGENE® assays in accurately detecting Gram-positive and Gram-negative pathogens when compared to traditional blood culture analysis systems, such as VITEK®. Methods: 819 Gram-positive and 373 Gram-negative blood samples were collected and tested using both VERIGENE® and VITEK®. Statistical tests were two-tailed and observations were defined as statistically significant if P ≤ 0.05. Results: VERIGENE® detected a pathogen in 816/819 (99.6%) samples of the Gram-positive blood cultures and 367/373 (98.3%) samples of the Gram-negatives compared to 805/819 (98.3%) and 367/373 (98.4%), respectively, using VITEK®. Gram-positive cultures had a sensitivity of 99.5% and a specificity of 27.3% (PPV 99.0%, NPV 42.9%, 98.7% accuracy) with VERIGENE analysis. Gramnegatives had a sensitivity of 99.2% and a specificity of 20.0% (PPV 98.9%, NPV 25.0%, 98.4% accuracy). Conclusion: Although statistically insignificant (P = 0.25), VERIGENE® was 1.3% more likely to identify Gram-positive bacteria when compared to conventional methods. Overall, we concluded that VERIGENE® assays are valuable in their ability to rapidly detect microorganisms and resistance markers, given their high sensitivities. This allows for select targeted therapy in patients with sepsis and can ultimately reduce mortality rates.
Keywords: VERIGENE®